STUDENTS AND HALAL CINEMA: LEISURE TIME, NEGOTIATION, AND HALAL AWARENESS - Muhammad Nur Said; Moh Mufid; Muhamad Ilham Mafatihul Ihda (Jurnal Analisa Sosiologi, 2025)
This study explores how Muslim students utilize their leisure time to enjoy entertainment at Cinépolis, a halal-certified cinema in Yogyakarta. The research focuses on value negotiation, moral flexibility, and the construction of religious identity amidst the dynamics of modernity. Employing a descriptive qualitative approach, data were collected through in-depth interviews and direct observation of students visiting the cinema. The findings reveal that students' choices are not merely driven by entertainment preferences but also reflect efforts to uphold religious values, including the selection of films, the management of prayer times, and interactions with the opposite gender. Halal entertainment options like Cinépolis illustrate the complex negotiation between the desire for recreation and the commitment to religious principles. Students demonstrate moral flexibility by considering the halal aspects of entertainment while navigating dilemmas such as films with adult scenes or schedules that conflict with prayer times. Furthermore, halal entertainment serves not only as a medium for relaxation but also as an expression of an adaptive religious identity, blending Islamic traditions with modernity. Halal cinemas provide a space for compromise where Islamic values can be preserved without disregarding the need for modern entertainment. This study contributes to the understanding of the role of halal entertainment in shaping the religious identity of Muslim youth and offers insights into how halal regulations in Indonesia influence entertainment choices. By highlighting the interplay between social and religious dimensions, the research underscores the dynamic interaction between religion, culture, and modernity in the lives of Muslim students.